2000
DOI: 10.1002/1098-1136(200012)32:3<286::aid-glia80>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

NMR spectroscopic study on the metabolic fate of [3-13C]alanine in astrocytes, neurons, and cocultures: Implications for glia-neuron interactions in neurotransmitter metabolism

Abstract: Nuclear magnetic resonance (NMR) spectroscopy and biochemical assays were used to study the fate of [3‐13C]alanine in astrocytes, neurons, and cocultures. 1H‐ and 13C‐NMR analysis of the media demonstrated a high and comparable uptake of [3‐13C]alanine by the cells. Thereafter, alanine is transaminated predominantly to [3‐13C]pyruvate, from which the 13C‐label undergoes different metabolic pathways in astrocytes and neurons: Lactate is almost exclusively synthesized in astrocytes, while in neurons and cocultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(65 citation statements)
references
References 68 publications
3
60
0
2
Order By: Relevance
“…Primary cell cultures of cortical astrocytes, cortical neurons, and cocultures of both cell types were obtained as described previously (Booher and Sensenbrenner, 1972;Zwingmann et al, 2000). Astrocytes were prepared from the brains of 1-or 2-day-old Sprague-Dawley rats and cultured in Dulbecco modified Eagle medium (DMEM) containing 10% fetal calf serum for 3 weeks.…”
Section: Cell Culturesmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary cell cultures of cortical astrocytes, cortical neurons, and cocultures of both cell types were obtained as described previously (Booher and Sensenbrenner, 1972;Zwingmann et al, 2000). Astrocytes were prepared from the brains of 1-or 2-day-old Sprague-Dawley rats and cultured in Dulbecco modified Eagle medium (DMEM) containing 10% fetal calf serum for 3 weeks.…”
Section: Cell Culturesmentioning
confidence: 99%
“…P-NMR spectra were analyzed with reference to the C-enrichments in individual carbons of amino acids are derived from 13 C-NMR spectra using the known 13 C-enrichment in lactate as described previously (Zwingmann et al, 2000):…”
mentioning
confidence: 99%
“…Indeed, these authors evidenced that the two pyruvate species, the glycolytic pyruvate and the pyruvate synthesized from exogenous lactate by lactate dehydrogenase, were compartmentalized and that the production of the first was inhibited when the second was used preferentially as an oxidative substrate. Moreover, the fact that alanine was synthesized in neurons suggested that it could be involved in the alanine-lactate shuttle between neurones and astrocytes (34,35), which might contribute to regenerating the cytoplasmic NAD ϩ in astrocytes through NADH oxidation by the respiratory chain in neurons.…”
Section: Involvement Of Brain Lactate In the Neuronal Metabolism-mentioning
confidence: 99%
“…Thus, cells may have increased their uptake of carbohydrates from the medium to account for higher energy metabolism. Neurons also have the ability to utilise alanine as an alternative energy source, which could explain the reduction in the level of alanine (Tables 3, 4) (Zwingmann et al 2000).…”
Section: Immunocytochemistry Of N1e-115 Cells Confirms Protein Expresmentioning
confidence: 99%